KERAGAMAN PADI GOGO LOKAL DI KABUPATEN BANYUMAS JAWA TENGAH - Oetami Dwi Hajoeningtijas; Agus Mulyadi Purnawanto (Universitas Muhammadiyah Purwokerto, 2013)
The potential of dry land which is functioned as cultivation of upland rice is expected to be able to create food autonomy in our country. Besides, for the development of the tree’s seed plasma to another location (ex situ) really requires the condition of the environment which resembles its in situ condition and for the need of preservation of the food tree’s seed plasma is really needed innovation of indigenous technology which is sufficient and easily absorbed by farmers. The problem arises when the seed of upland rice with various best qualities is difficult to find. Therefore, it really requires the identification of local upland rice either as the glorification material or to be developed through cultivation by using its various best qualities. The result of this research is expected to be able to preserve the local upland rice seed plasma as well as capable of recognizing varieties of local upland rice then known the strength and the uniqueness of each variety so that it can be used as guidance for the farmers to be planted or for the researchers as the genetic material. The research was conducted in districts in Banyumas regency which is previously done the initial survey to obtain suitable local information. The research was done from April to July, 2013 (for four months). The research used survey method with qualitative approach. Basic method in the research is descriptive analysis method. The data collection was done by using survey, that is the way of collecting the data using observation or investigation to get clear explanation and either toward a certain problem in a region or in certain regions. Based on the result of the research, it can be concluded that in the mean time variety of upland rice which is mostly cultivated by the farmers in Bamyumas regency is Situbagendit, Situpatenggang, and Ciherang variety. Besides, there are 13 varieties of Banyumas local rice extinct as the result of not to be cultivated intensively, that are Hitam rice, Gandamana rice, Kidangsari rice, Konyal rice, Cere Unggul rice, Cere Kuning rice, Sari Wangi rice, Pandan Wangi rice, Mentik Wangi rice, Mentik rice, Mendali rice, Sri Wulan rice, Wangi Lokal rice (some are potentially developed as upland rice) are high production, short age, resistance of plant disease. Meanwhile, for Situ Patenggang rather resists of dryness. Keywords: Diversity, upland rice, local, Banyumas